Avaliação econômico-ecológica do Núcleo Social de Gestão do Agroecossistema (NSGA) “Sítio Dossel”, a partir da implantação de sistemas agroflorestais sucessionais (2018 a 2024): uma contribuição para o debate sobre soberania alimentar e autonomia camponesa. - Gregio, Josue Vicente (2025)
Given the increasing importance of actions that contribute to strengthening synergies in the society-nature relationship and to substantial changes in the way food is produced, successional agroforestry, which is based on Ernst Götsch's syntropic farming, presents itself as an agroecological spatial practice that allows food production to be compatible with forest restoration processes, through agroforestry systems based on the natural succession of plant species. In this sense, the general objective of this thesis is to analyze and systematize the experience of implementing agroforestry systems at Sítio Dossel, located in the municipality of Sananduva, Rio Grande do Sul, which began in 2016. The theoretical basis of the research was based on bibliographic references concerning: 1) a history of food production, emphasizing agribusiness (hegemonic food system) and agroecology as a counterpoint; 2) the debate on food security, food sovereignty and peasant autonomy; and 3) the principles of syntropy and syntropic farming. From a methodological point of view, the assessment of the Agroecosystem/Social Center for Agroecosystem Management (NSGA) Sítio Dossel was carried out through the application of the LUME Method – developed by Petersen et al. (2017), with the contribution of organizations involved with the National Articulation of Agroecology (ANA) and the Brazilian Semi-Arid Articulation (ASA) – which consists of the economic-ecological analysis of agroecosystems, enabling the generation of data based on the products, inputs, labor and flows of the agroecosystem. The application of this method was planned for three moments within the scope of the NSGA Sítio Dossel: 2018, 2021 and 2024, in order to demonstrate the changes that occurred after seven years of agroforestry implementation and management practices based on syntropic farming. Furthermore, a more qualitative assessment of the benefits arising from work with agroforestry was made, in terms of elements that indicate peasant autonomy, based on Candiotto‟s proposal (2019 and 2023a), which considers seven dimensions of the debate on agroecology. Through the explanation of the dynamics of the NSGA at three different times, as well as the comparison between 2018 and 2024, it was possible to verify, quantitatively and qualitatively, the degrees of recovery and environmental conservation achieved and, above all, an abundant production of agroecological foods resulting from agroforestry management, which are directly linked to the strengthening of food sovereignty and peasant autonomy.